Pengaruh pendidikan agama islam terhadap pembentukan karakter religius siswa - Khanifah, Nuha Nafi'atul (Maliki Interdisciplinary Journal, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' religious character, particularly amidst the moral challenges of the modern era. This study aims to examine the influence of PAI on religious character formation in schools using a descriptive-qualitative approach through a literature review of various scientific sources. The study's results indicate that the success of PAI is determined not only by the subject matter, but also by the teacher's exemplary conduct, a religious school atmosphere, and active and enjoyable learning methods. PAI should not only focus on religious knowledge but also instill spiritual, moral, and ethical values ​​that can be applied in students' daily lives. If religious education is implemented optimally, PAI can become a strategic tool for producing a generation with faith, noble character, and the ability to face the challenges of the times by adhering to Islamic values.